Engineering wireless-based software systems and applications - Gao, Jerry (Artech House computing library., 2006)
Presenting the state-of-the-art in component-based software testing, this new, cutting-edge resource offers you an in-depth understanding of the current issues, challenges, needs, and solutions in this critical area. The book discusses the very latest advances in component-based testing and quality assurance in an accessible tutorial format, making the material easy to comprehend and benefit from no matter what your professional level.